Clinical significance of frusemide stress test in predicting the severity of acute kidney injury - Pon,Arun Gokul (2021)
Abstract Introduction: The outcomes of Acute Kidney Injury (AKI) remain dismal even today, owing in part due to the lack of an ideal biomarker for detecting renal damage early enough. We conducted this pilot study to determine the clinical significance of Frusemide Stress Test (FST) to predict the severity of AKI. Methods: A total of 80 patients with AKI-KDIGO (Kidney Disease: Improving Global Outcomes) stage 1 or stage 2 underwent FST by administering a bolus dose of frusemide (1mg/kg for frusemide naïve and 1.5mg/kg for prior frusemide exposure in the past week), and urine output was then measured for the next two hours with volume replacement as desirable. The progression to AKI-KDIGO stage 3 within 14 days of FST was studied as the primary outcome. The composite end point of achieving AKI-KDIGO stage 3 or death within 14 days of FST was studied as the secondary outcome. Results: Out of 80 patients, 28(35%) patients met the primary outcome, and 34(42.5%) patients met the secondary composite outcome. Except for baseline Chronic Kidney Disease (CKD) status (p=0.018), other demographic characteristics were comparable between progressors and non-progressors group. Using receiver operating characteristics (ROC) curve analysis, a cumulative 2-hour post-FST urine output of ≤300 mL predicted progression to stage 3 AKI with 82.14% sensitivity, 82.69% specificity, and AUC of 0.89±0.03 (p<0.0001). Conclusion: The FST showed promising results as a novel tubular biomarker to identify progression to severe AKI with good predictive ability.